Design and Characteristics of various types of gas sensors for hydrogen sulfide gas detection - A Review. Issue 1 (1st May 2022) - Sheoran, Jyoti; Kumar, Rajesh
Abstract: This paper reviews the sensor design and the gas sensing characteristics such as stability, sensitivity, response time, range of operation etc. to detect and monitor highly toxic gas such as hydrogen sulfide. This gas is responsible for many deaths in the industrial environments and flaura and fauna of a region. The comparison between the gas sensors can be done on the basis of operating range of gas concentration and working principle. Also the various limitations of each gas sensor has been discussed. From this study the best possible materials that give best possible characteristics for the hydrogen sulfide gas sensor fabrication have been identified. Using this knowledge, a highly sensitive and selective gas sensor that will have industrial uses too will be fabricated.